Non-specific skin purpura - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada (Academy of Family Physicians of Malaysia, 2018)
Essential thrombocythemia is one of the myeloproliferative neoplasms. Palpable purpura is a rare manifestation that may delay diagnosis and treatment. We report a case of essential thrombocythemia in a 50-year-old man, who presented with recurrent thigh pain for the past one year with nonspecific localized purpura. His full blood count revealed isolated thrombocytosis of 880,000/µL with an impression of myeloproliferative disorder from peripheral blood film. He was referred urgently to the hematology team, which proceeded with a venesection. His condition improved with hydroxyurea. This was a rare case of chronic presentation of myeloproliferative neoplasm detected at a primary care clinic.